Avaliação do lapachol radiomarcado com tecnécio-99m como marcador tumoral e desenvolvimento e caracterização de nanoemulsão contendo lapachol - Sued Eustaquio Mendes Miranda (2018)
Cancer is considered a public health problem, in 2018/2019 is expected 600,000 new cases being breast cancer responsible for 28%. Due to the high incidence and mortality, new alternatives have been sought for the treatment and diagnosis of this disease. In recent years, the search for substances with antitumor activity has increased and some classes of compounds have received a lot of interest, such as naphthoquinones. Lapachol is a naphthoquinone used since the late twentieth century in the treatment of various diseases, including certain types of cancer that have been brought to stage 2 clinical trials for the treatment of Yoshida's sarcoma and Walker 256 carcinoma, but its study was canceled because of especially their low plasma concentration. In this context, the objective of this work was to perform radiochemistry with technetium-99m and biodistribution studies of lapachol in a breast tumor experimental model, as well as to prepare and characterize a nanoformulation containing lapachol for further studies on the treatment of breast tumors. The results demonstrated that lapachol can be labeled with high radiochemical purity (95.9% ± 3.4%), and the labeling remained stable for up to 24 hours. Subsequent studies indicated hydrophilic character (partition coefficient -1.55 ± 0.17) for the 99mTc-lapachol complex with high plasma protein binding rate (approximately 90%). In vivo studies indicated biphasic clearance with distribution and elimination half-lives of 4 and 54 minutes, respectively. Biodistribution and scintigraphic images in breast tumor-bearing mice showed high uptake in organs of excretion and greater accumulation in the tumor region when compared to the contralateral muscle. The lapachol-loading nanoemulsion was successfully prepared showing size and encapsulation percentage compatible with intravenous administration. Preliminary studies indicated stability of the formulation at the concentration 0.5 mg/mL for up to 7 days. The formulation was radiolabeled with 99mTc exhibiting high radiochemical purity (94.5 ± 1.3%) and high stability up to 24 hours. Therefore, the 99mTc-lapachol complex presents promising characteristics for a potential breast cancer diagnostic agent and the prepared formulation can be used in future studies to evaluate the antitumor potential of lapachol.